Developmental and activity-dependent plasticity of filiform hair receptors in the locust - Pflüger, Hans-Joachim; Wolf, Harald (Frontiers in Physiology, 2013)
A group of wind sensitive filiform hair receptors on the locust thorax and head makes contact onto a pair of identified interneuron, A4I1. The hair receptors’ central nervous projections exhibit pronounced structural dynamics during nymphal development, for example, by gradually eliminating their ipsilateral dendritic field while maintaining the contralateral one. These changes are dependent not only on hormones controlling development but on neuronal activity as well. The hair-to-interneuron system has remarkably high gain (close to 1) and makes contact to flight steering muscles. During stationary flight in front of a wind tunnel, interneuron A4I1 is active in the wing beat rhythm, and in addition it responds strongly to stimulation of sensory hairs in its receptive field. A role of the hair-to-interneuron in flight steering is thus suggested. This system appears suitable for further study of developmental and activity-dependent plasticity in a sensorimotor context with known connectivity patterns.